Material characterisation of biaxial glass-fibre non-crimp fabrics as a function of ply orientation, stitch pattern, stitch length and stitch tension. (November 2022) - Quenzel, Philipp; Kröger, Hauke; Manin, Boris; Ngoc Vu, Khiêm; Duong, Thang Xuan; Gries, Thomas; Itskov, Mikhail; Sauer, Roger A.
Due to their high density-specific stiffnesses and strength, fibre reinforced plastic (FRP) composites are particularly interesting for mobility and transport applications. Warp-knitted non-crimp fabrics (NCF) are one possible way to produce such FRP composites. They are advantageous because of their low production costs and the ability to tailor the properties of the textile to the reinforcement and drape requirements of the application. Based on their specific production parameters, their draping properties can vary significantly. Draping simulations are used to predict the forming behaviour without relying on costly and time consuming trial and error experiments. However, these simulations require a broad material dataset to make accurate predictions. Previous studies have investigated the relationships between production parameters and drape behaviour only in isolation for a limited number of material parameters at a time. In this study, a comprehensive material characterisation is carried out. The influence of ply orientation, stitch pattern, stitch length and stitch tension on the tensile and bending properties and the friction, shear and drape behaviour of NCFs are investigated on a meso and macro scale. Furthermore, the inter-ply sliding phenomena in bias extension tests are analysed and the results of bias extension and picture frame tests are compared.